PERSPEKTIF ORANGTUA SISWA SEKOLAH DASAR TERHADAP PENGGUNAAN SOSIAL MEDIA - Indah Wahyuningsih, Putri; Tuningsih, Suci (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study result to find out the perspectives of parents of elementary school students on the use of social media. The research method used is qualitative phenomenology by collecting data through interviews with parents of elementary school students. The results of the study show that from various perspectives of parents of elementary school students at SDN Rejosari 03 there are positive, negative or neutral results. The use of social media has both positive and negative impacts. Children at SDN Rejosari 03 use social media not only for chatting and watching videos on YouTube or TikTok but also for searching for sources of information from Google. The positive impact of using social media provides convenience for children and parents, especially for school or learning purposes, and children can be digitally literate from an early age. However, the negative impact of using social media is a concern and anxiety for parents of elementary school students.